Image Transmission Over Erroneous Wireless mobile Channels using HQAM Techniques - Ashrf Alzrouk Almagdob, Ahmed B. Abdurrhman, Ibrahim A.Nasir, Weal Saleh Abughres (Journal of Pure & Applied Sciences, 2020)
This paper examines the process of sending an image over wireless mobile Channels with errors while maintaining bandwidth, transmission speed and image quality. With the tremendous development in networks, new wireless channels have been opened that threaten the security of data transmitted through networks and communication channels, and from this emerged Encryption techniques to increase the security of the transmitted data, and since the digital image compression algorithm is a process to reassemble the parts of the image so that it takes less space, but this increases the impact of the error extension in sending compressed digital images and greatly reduces the quality of the received image. This prompts us in this paper to study the performance of HQAM technology for the purpose of transmitting image data over wireless communication channels containing errors. In this paper, image quality performance has been evaluated by the BER, SNR, PSNR, SSIM, and Correlation evaluation criteria. The simulated results show that there is an improvement in the image quality received using the proposed technique.